Healthy lifestyle, statin, and mortality in people with high CVD risk: A nationwide population-based cohort study - Wenyao Peng; Xueke Bai; Yang Yang; Jianlan Cui; Wei Xu; Lijuan Song; Hao Yang; Wenyan He; Yan Zhang; Xingyi Zhang; Xi Li; Jiapeng Lu (American Journal of Preventive Cardiology, 2024)
Abstact: Objective: To examine the joint association of healthy lifestyles and statin use with all-cause and cardiovascular mortality in high-risk individuals, and evaluate the survival benefits by life expectancy. Methods: During 2015–2021, participants aged 35–75 years were recruited by the China Health Evaluation And risk Reduction through nationwide Teamwork. Based on number of healthy lifestyles related to smoking, alcohol drinking, physical activity, and diet, we categorized them into: very healthy (3–4), healthy (2), and unhealthy (0–1). Statin use was determined by self-report taking statin in last two weeks. Results: Among the 265,209 included participants at high risk, 6979 deaths were observed, including 3236 CVD deaths during a median 3.6 years of follow-up. Individuals taking statin and with a very healthy lifestyle had the lowest risk of all-cause (HR: 0.70; 95 %CI: 0.57–0.87) and cardiovascular mortality (0.56; 0.40–0.79), compared with statin non-users with an unhealthy lifestyle. High-risk participants taking statin and with a very healthy lifestyle had the highest years of life gained (5.90 years at 35-year-old [4.14–7.67; P < 0.001]) compared with statin non-users with an unhealthy lifestyle among high-risk people. And their life expectancy was comparable with those without high risk but with a very healthy lifestyle (4.49 vs. 4.68 years). Conclusion: The combination of preventive medication and multiple healthy lifestyles was associated with lower risk of all-cause and cardiovascular mortality and largest survival benefits. Integrated strategy to improve long-term health for high-risk people was urgently needed.